2018
DOI: 10.1515/hc-2018-0117
|View full text |Cite
|
Sign up to set email alerts
|

An efficient synthesis of imidazo[2,1-b][1,3,4]thiadiazol-7-ium hydroxides by a one-pot, three-component reaction in water

Abstract: An improved synthesis of 2-ethyl-5-(2-hydroxy-4-oxoquinolin-3(4H)-ylidene)-6-aryl-5,6-dihydroimidazo[2,1-b][1,3,4]thiadiazol-7-ium hydroxide derivatives 4a–k via the reaction of aryl glyoxal monohydrates 1a–k, quinoline-2,4-diol 2 and 2-amino-[1,3,4]thiadiazole (3) in the presence of Et3N/sulfamic acid in H2O is described. This green protocol is characterized by the use of the readily available catalyst and reactants, short reaction times, operational simplicity and high yields of products. The structures of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…In recent years, a diverse set of 1,3,4-thiadiazole analogs have been developed, exhibiting a broad spectrum of biological activities, such as antiparasitic ( 13 ), anticancer ( 14 ), antibacterial ( 15 ), antiviral ( 16 ), and antitubercular ( 17 - 19 ) activities. Furthermore, several studies on molecules with antiplatelet activity have revealed that analogs containing N -acylhydrazone and its isosteres exhibit remarkable antiplatelet activity ( 3 , 20 - 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a diverse set of 1,3,4-thiadiazole analogs have been developed, exhibiting a broad spectrum of biological activities, such as antiparasitic ( 13 ), anticancer ( 14 ), antibacterial ( 15 ), antiviral ( 16 ), and antitubercular ( 17 - 19 ) activities. Furthermore, several studies on molecules with antiplatelet activity have revealed that analogs containing N -acylhydrazone and its isosteres exhibit remarkable antiplatelet activity ( 3 , 20 - 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…The imidazo[2,1-b] [1,3,4]thiadiazole bicycle system has imidazole and 1,3,4-thiadiazole moieties. [12] Many imidazoles have been used since more than 70 years ago as Carbonic anhydrase inhibitor(CAI). Based on imidazo[2,1b] [1,3,4]thiadiazole ring [13] medications have been used in therapeutics, including acetazolamide, methazolamide, ethoxzolamide, and dorzolamide.…”
Section: Introductionmentioning
confidence: 99%